PENGARUH PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR PENGETAHUAN BAHAN SENI RUPA SISWA KELAS XI SMKN 4 PADANG - SISKA FRENIKE, Dr. Ramalis Hakin, M.Pd., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2017)
This study aims to determine the effect of the application of cooperative learning type Numbered Heads Together (NHT) the learning outcomes of Materials Science Art 4 class XI student of SMK Padang. The research is a quasi-experimental (quasi ekspermental) with racangan research is pretest posttest control group design. Retrieving data using purposive sampling technique. Data were collected by achievement test. The findings in this study show that: using cooperative learning model NHT shows a high learning outcomes when compared to using conventional learning models. This means that the implementation of cooperative learning model NHT positive effect on learning outcomes Materials Sciences Arts XI class at SMK Padang 4. It can be concluded that the use of cooperative learning model NHT in learning is needed by every educator in order to improve student learning outcomes, especially in the subjects of Materials Sciences Arts at SMK Padang 4.Kata kunci: Model pembelajaran kooperatif tipe NHT